Letter from E.N. Horsford to James Curtis Booth, April 3, 1854 - Horsford, Eben Norton (1854)
Eben Norton Horsford (1818-1893), a Harvard professor of agricultural chemistry, writes to James Curtis Booth (1810-1888) to inquire about courses offered by Booth.
Keywords: Booth, James Curtis, 1810-1888; Horsford, Eben Norton, 1818-1893; Lectures and lecturing; Chemistry teachers